2015
DOI: 10.1117/12.2085683
|View full text |Cite
|
Sign up to set email alerts
|

9nm node wafer defect inspection using three-dimensional scanning, a 405nm diode laser, and a broadband source

Abstract: We recently built a 405nm laser based optical interferometry system for 9nm node patterned wafer defect inspection. Defects with volumes smaller than 15nm by 90nm by 35nm have been detected. The success of defect detection relied on accurate mechanical scanning of the wafer and custom engineered image denoising post-processing. To further improve the detection sensitivity, we designed a higher precision XYZ scanning stage and replaced the laser source with an incoherent LED to remove the speckle noise. With th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The rapid and precise imaging of three-dimensional (3D) semiconductor devices is of significant importance for semiconductor wafer inspection during the manufacturing process. In general, imaging techniques can be classified into two types, namely two-dimensional (2D) inspection and 3D inspection 1,2 . Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) are techniques that can identify defects and measure the critical dimension (CD) of fine patterns in highresolution 2D images 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…The rapid and precise imaging of three-dimensional (3D) semiconductor devices is of significant importance for semiconductor wafer inspection during the manufacturing process. In general, imaging techniques can be classified into two types, namely two-dimensional (2D) inspection and 3D inspection 1,2 . Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) are techniques that can identify defects and measure the critical dimension (CD) of fine patterns in highresolution 2D images 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…N. T. Shaked et al [14] reported placing the interferometer in a vacuum-sealed enclosure to avoid the influence of the air flow and used a floating optical table to damp the device oscillations to some extent. R. Zhou et al [15] explored the use of high stability laser sources (i.e., temperature and current controlled semiconductor lasers) and broadband light sources to minimize the phase noise. G. Popescu et al [16] developed diffraction phase microscopy (DPM) with a common-path off-axis interferometry geometry to diminish the mechanical vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Many defect inspection tools rely on the wafer periodic pattern and subtract between seemingly similar areas on the wafer along the defect inspection pipeline. The subtraction image enhances irregularities in the wafer pattern, and, if any defect is present, it will be revealed in the subtraction image, given the defect signal is stronger than the noise of the subtracted periodic pattern [3][4][5][6][7][8]. It is therefore important to enhance the defect signal over the pattern signal, as early as possible, hopefully during the image acquisition stage of the inspected area.…”
Section: Introductionmentioning
confidence: 99%
“…When imaging wafers, the phase distribution of an optical wave reflecting from the wafer indicates its surface topography. Irregularities in the wafer topography indicate defects in the wafer fabrication process [3,4,[9][10][11] and can damage the final semiconductor device. Without imaging phase variations, vital information about the wafer pattern is lost.…”
Section: Introductionmentioning
confidence: 99%